AFAP1-AS1 regulates oral squamous cell carcinoma development through the miR-93-3p/CCND1 signaling pathway - Kuangzheng Li; Chengwei Li; Qian He; Xiaosheng Fan; Lili Xu; Yixia Jiang (Mammalian Genome, 2026)

Designing hard-soft carbon composite anodes via a normalized pore volume-mass matching strategy for high-performance sodium storage - Xiaoqi Yu; Xiaoyu Xu; Hanyu Wei; Xiaofeng Zhang; Haiyan Liu; Chengwei Fan; Ang Li; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2026)

Passive atmospheric wind profile retrieval via multi-region microwave radiometer network - Shuailong Jiang; Yingying Ma; Chengwei Li; Lianfa Lei; Boming Liu; Shikuan Jin; Hui Li; Weiyan Wang; Ruonan Fan; Yujie Wang; Ao Miao; Wei Gong (Atmospheric Research, 2026)

Single channel tactile sensor array for detection of pressure and position with two electrodes - Jingwen Xing; Tingkang Yuan; Shenqi Yang; Chengwei Li; Zeng Fan; Lujun Pan (Chemical Engineering Journal, 2025)

The response mechanisms of kelp Macrocystis pyrifera holobiont to elevated temperature and CO2 concentration - Tianle Xi; Yajing Liu; Xiaowen Zhang; Shanshan Ge; Yitao Wang; Ke Sun; Xiao Fan; Dong Xu; Pengyan Zhang; Chengwei Liang; Naihao Ye (Journal of Applied Phycology, 2025)

Corrigendum to “Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries” [Mar. Environ. Res. 204 (2025) 106901] - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

A Shikonin-Iron-Tragacanth gum nanocomplex for synergistic treatment of bladder cancer - Kangkang Zhao; Jianlun Hu; Hailong Zhang; Tianyi Chen; Shuyang Yang; Hao Wang; Fan Wu; Hao Hong; Gutian Zhang; Chengwei Zhang (Chemical Engineering Journal, 2025)

Pathological Progress of Two Types of Nodules in Micropterus salmoides Infected with Nocardia seriolae - Chengwei Li; Wenhui Wang; Fan Wu; Hao Pu; Lei Liao (Fishes, 2024)
The typical clinical signs of Nocardia seriolae infection include white nodules, ranging from 0.1 to 10 mm in diameter, distributed across various internal organs. However, the structural composition of nodules of different sizes remains unexplored. In this study, natural cases of largemouth bass (Micropterus salmoides) were collected, and pathogenic bacteria were isolated and confirmed through a re-infection experiment. The isolated bacteria were identified as N. seriolae through 16S rRNA and gyrB gene sequencing. Healthy largemouth bass were infected with the isolate using an immersion infection and observed continuously over 56 days. Samples were successfully obtained from the incubation, prodromal, symptomatic, and convalescent phases, allowing for gross, histological, and ultrastructural observations of nodular lesion progression. Results demonstrated two types of nodular lesions: necrotic foci and granulomas. Macroscopically visible nodules larger than 1 mm, observed primarily in the liver, spleen, kidney, and muscle tissues of moribund fish, exhibited coagulative necrosis and were identified as the principal cause of mortality. Conversely, granulomas, with diameters less than 1 mm, were consistently present in the spleen, kidney, and liver during the symptomatic and convalescent phases.

Alleviative effects of C60 fullerene nanoparticles on arsenate transformation and toxicity to Danio rerio - Xiaoyan Wang; Zhaomin Dong; Qing Zhao; Chengwei Li; Wen-Hong Fan (Science of The Total Environment, 2024)

Integration of carbon microsheets and helical carbon nanocoils for efficient microwave absorption - Chen Sun; Hao Zhang; Xueqing Zuo; Yuchen Jiang; Yifeng Zhang; Chengwei Li; Zeng Fan; Lujun Pan (Chemical Engineering Journal, 2024)

Geometrically asymmetric pressure sensor with precious few electrodes achieves precise detection of both position and strength by machine learning - Tingkang Yuan; Ruilin Yin; Chengwei Li; Zeng Fan; Lujun Pan (Chemical Engineering Journal, 2024)

Antifungal efficacy of Bacillus amyloliquefaciens ZK-9 against Fusarium graminearum and analysis of the potential mechanism of its lipopeptides - Yanjie Yi; Pengyu Luan; Minghao Fan; Xingquan Wu; Zhongke Sun; Zijun Shang; Yuzhen Yang; Chengwei Li (International Journal of Food Microbiology, 2024)

Ultra-Flexible microwave absorber of PEDOT:PSS/Melamine composite film with wide tunable frequency controlled by Self-Strain sensing - Xueqing Zuo; Cao Zhou; Tingkang Yuan; Ningxuan Wen; Chen Sun; Hao Zhang; Yifeng Zhang; Jie Tian; Chengwei Li; Zeng Fan; Lujun Pan (Chemical Engineering Journal, 2024)

Ti3C2Tx MXene-based all-resistive dual-mode sensor with near-zero temperature coefficient of resistance for crosstalk-free pressure and temperature detections - Tingkang Yuan; Ruilin Yin; Chengwei Li; Zeng Fan; Lujun Pan (Chemical Engineering Journal, 2024)

The impact of induced pluripotent stem cells in animal conservation - Yurou Wu; Chengwei Wang; Xinyun Fan; Yuxiao Ma; Zibo Liu; Xun Ye; Chongyang Shen; Chunjie Wu (Veterinary Research Communications, 2024)

Green and rapid synthesis of hierarchical nano-sized pure Si-Beta zeolite supported with Zn and Y for effective synthesis of butadiene from aqueous ethanol - Kangzhou Wang; Chong Chen; Weizhe Gao; Na Liu; Chengwei Wang; Fan Wang; Jiaqi Fan; Yongqiang Gu; Caixia Zhu; Noritatsu Tsubaki (Chemical Engineering Journal, 2024)

Pipelines reliability assessment considering corrosion-related failure modes and probability distributions characteristic using subset simulation - Changjun Li; Fan Yang; Wenlong Jia; Chengwei Liu; Jianghao Zeng; Shuoshuo Song; Yuanrui Zhang (Process Safety and Environmental Protection, 2023)

Fully inkjet-printed dual-mode sensor for simultaneous pressure and temperature sensing with high decoupling - Tingkang Yuan; Ruilin Yin; Chengwei Li; Chao Wang; Zeng Fan; Lujun Pan (Chemical Engineering Journal, 2023)

A novel evaluation method for rolling energy losses of tacked vehicle road wheels using experimental modal analysis - Chengwei Zhu; Ye Zhuang; Weiguang Fan; Zhenxin Long; Shuyu Zhang (Journal of Terramechanics, 2023)

Acute effects of three surface-modified nanoplastics against Microcystis aeruginosa: Growth, microcystin production, and mechanisms - Xiaowei Zheng; Liangliang Zhang; Chao Jiang; Jue Li; Yanyao Li; Xianglin Liu; Chengwei Li; Zeming Wang; Nan Zheng; Zhengqiu Fan (Science of The Total Environment, 2023)

Identification of genes under positive selection reveals evolutionary adaptation of Ulva mutabilis - Jian Zhang; Xiaowen Zhang; Wentao Han; Xiao Fan; Yitao Wang; Dong Xu; Yan Zhang; Jian Ma; Chengwei Liang; Naihao Ye (Acta Oceanologica Sinica, 2020)

Characterization of a broad substrates specificity acyl-CoA: diacylglycerol acyltransferase 1 from the green tide alga Ulva prolifera - Xiaowen Zhang; Xiaoyuan Chi; Yitao Wang; Jian Zhang; Yan Zhang; Dong Xu; Xiao Fan; Chengwei Liang; Naihao Ye (Acta Oceanologica Sinica, 2020)

Different physiological and molecular responses of the green algae Chlorella variabilis to long-term and short-term elevated CO2 - Chengwei Liang; Xiao Yang; Lu Wang; Xiao Fan; Xiaowen Zhang; Dong Xu; Naihao Ye (Journal of Applied Phycology, 2020)

Development of a high spatiotemporal resolution cloud-type classification approach using Himawari-8 and CloudSat - Chengwei Zhang; Xiaoyong Zhuge; Fan Yu (International Journal of Remote Sensing, 2019)

Isolation and expression analyses of methyl-d-erythritol 4-phosphate (MEP) pathway genes from Haematococcus pluvialis - Chengwei Liang; Wei Zhang; Xiaowen Zhang; Xiao Fan; Dong Xu; Naihao Ye; Zhongliang Su; Jiansheng Yu; Qingli Yang (Journal of Applied Phycology, 2016)

Transplantation of microencapsulated Schwann cells and mesenchymal stem cells augment angiogenesis and improve heart function - Yan Wang; Gang Zhang; Yongbo Hou; Jian Chen; Juan Wang; Chengwei Zou; Decai Li; Hongxin Li; Qian Zhang; Anbiao Wang; Quanxin Fan (Molecular and Cellular Biochemistry, 2012)

Three-dimensional extension of the unit-feature spatial classification method for cloud type - Chengwei Zhang; Fan Yu; Chenxi Wang; Jianyu Yang (Advances in Atmospheric Sciences, 2011)